(untitled) (Minerva, 2019)
This article seeks to describe the sociolinguistic situation of modern Greece during the period from 1830 to 1941. Thanks to Charles Ferguson, this situation has been traditionally viewed as a example of diglossia. However, other autors have argued that Ferguson’s diglossia does not correspond with modern Greece. Therefore, Lamuela’s survey of the social roles of languages (symbolic, definitory, and communicative), which stands as a valuable alternative to Ferguson’s scheme of diglossia, has been used in this article. As a conclusion, the linguistic situation of modern Greece after 1830 can be seen as a linguistic culture where the writen tradition became the most important national value. Only at the end of XIX century demoticists attempted to develop an alternative national language and presented Greece as a diglossic community.